Design of low inductance switching power cell for GaN HEMT based inverter - Gurpinar, Emre; Iannuzzo, Francesco; Yang, Yongheng; Castellazzi, Alberto; Blaabjerg, Frede (IEEE, 2017)
In this paper, an ultra-low inductance power cell is designed for a three-Level Active Neutral Point Clamped (3LANPC) based on 650 V gallium nitride (GaN) HEMT devices. The 3L-ANPC topology with GaN HEMT devices and the selected modulation scheme suitable for wide-bandgap (WBG) devices are presented. The commutation loops, which mainly contribute to voltage overshoots and increase of switching losses, are discussed. The ultra-low inductance power cell design based on a fourlayer Printed Circuit Board (PCB) with the aim to maximize the switching performance of GaN HEMTs is explained. The design of gate drivers for the GaN HEMT devices is presented. Parasitic inductance and resistance of the proposed design are extracted with finite element analysis and discussed. Commonmode behaviours based on the SPICE model of the converter are analyzed. Experimental results on the designed 3L-ANPC with the output power of up to 1 kW are presented, which verifies the performance of the proposed design in terms of ultra-low inductance.